EXPLORING THE PHILOSOPHY OF LANGUAGE: SCOPE, HISTORY, AND ITS CONNECTIONS WITH CULTURE AND LITERATURE - Solo, Lenny; Nuruddin (Dialectical Literature and Educational Journal, 2024)
This research focuses on the importance of the philosophy of language in understanding the relationship between language, reality, culture, and human communication. This study was conducted using a qualitative approach with a descriptive-analytical approach. Data was collected through literature studies and analysis of primary literature in the philosophy of language, covering theories of epistemology, ontology, and axiology in the context of language. Philosophy, which comes from the Greek words "philia" and "sophia," etymologically means the love of wisdom. One important branch of philosophy is the philosophy of language, which aims to explore how language shapes meaning, how language represents reality, and how language plays a role in communication and understanding between humans. Through this study, we understand how philosophers like Noam Chomsky, J.L. Austin, and Hans-Georg Gadamer highlight language as an instrument of thought and a tool for expressing ideas and cultural identity. Philosophy of language also examines the role of language in social, political, and cultural contexts, as well as how language is used to preserve, negotiate, or manipulate reality and identity.